Comparative morphology of the anterior end of selected taxa of Merliniidae Siddiqi, 1971 (Nematoda: Tylenchoidea), with morphological characterisation of two species and taxonomic keys to several genera - Ghaderi, Reza; Karegar, Akbar; Miraeiz, Esmaeil; Hashemi, Kobra (Zootaxa, 2017)
Comparative morphology of the anterior end is used to characterise certain genera and species of the family Merliniidae, based on populations of 18 species collected from different localities in Iran. We discuss the importance of anterior end morphology in separating Pratylenchoides from Amplimerlinius, and Paramerlinius from Merlinius and Nagelus, as well as for identifying species in the genera Amplimerlinius, Merlinius and Geocenamus. Furthermore, descriptions, morphometric data, line drawings and photomicrographs are provided for Pratylenchoides leiocauda and Telotylenchus paaloofi as new records for the Iranian nematode fauna. Finally, updated species identification keys for the genera Macrotylenchus, Merlinius, Nagelus and Paramerlinius are given.